2015
DOI: 10.1590/0102-311x00210913
|View full text |Cite
|
Sign up to set email alerts
|

Association of perceived neighborhood problems and census tract income with poor self-rated health in adults: a multilevel approach

Abstract: Neighborhood problems constitute sources of chronic stress that may increase the risk of poor self-rated health. The associations of census tract level income and perceived neighborhood problems with self-rated health were examined in Florianópolis, Santa Catarina State, Brazil (1,720 adults). Odds ratios (OR) and their 95% confidence intervals (95%CI) of poor self-rated health were estimated through multilevel models. Residents in census tracts in the lower and intermediate tertiles of income reported poorer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…In this study, “citizens’ services,” a factor related to women’s general health, refers to the respondents’ perceived access to a family health center, as well as the extent of opportunities for community participation in plans and events within the neighborhood. These findings are consistent with two studies from Brazil demonstrating links between the quality of public services and better self-reported health [ 5 , 16 ]. Prioritizing the early availability of good citizens’ services in new neighborhoods may help deliver better self-reported general health for their residents.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, “citizens’ services,” a factor related to women’s general health, refers to the respondents’ perceived access to a family health center, as well as the extent of opportunities for community participation in plans and events within the neighborhood. These findings are consistent with two studies from Brazil demonstrating links between the quality of public services and better self-reported health [ 5 , 16 ]. Prioritizing the early availability of good citizens’ services in new neighborhoods may help deliver better self-reported general health for their residents.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with studies in countries of the global North and other countries in Latin America that showed an association between perceived physical disorder and self-rated health [12,[28][29][30][31]. Poortinga and colleagues found that urban environment characteristics, such as litter and rubbish; vandalism; and discarded needles and syringes, had the strongest associations with poor health at the neighborhood level in Wales, United Kingdom [28].…”
Section: Discussionsupporting
confidence: 84%
“…Poortinga and colleagues found that urban environment characteristics, such as litter and rubbish; vandalism; and discarded needles and syringes, had the strongest associations with poor health at the neighborhood level in Wales, United Kingdom [28]. In Brazil, researchers observed that perceived physical disorder, such as garbage; presence of graffiti; vacant lots; vandalism; street lighting, were also associated with poor self-rated health [12,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations